PENGEMBANGAN ASSESSMENT READING BERBASIS HOTS UNTUK OPTIMALISASI KEMAMPUAN LITERASI - Dian Mega Putri; Dian Noviani Syafar (JUPADAI : Jurnal Pengabdian Kepada Masyarakat, 2022)
The essential role of professional teacher in teaching and learning process is a key in achieving successful learning outcome. A professional teacher is a competent teacher who is able to build and develop good and effective teaching and learning process in order to create smart and good quality students. Based on the observation and previous study done by some experts, there are many teachers who still face difficulties in creating HOTS based Reading Assessment that can develop students higher thinking skills. So that, a workshop and training about HOTS’ based assessment of reading need to be deliver to teachers. This training and workshop was done in SMP N 33 Padang in 2 types of activity; the workshop about reading assessment and training of reading assessment of HOTS (Higher Order Thinking Skill) Based. This activity is very essential and helpful for teachers in order to enrich their knowledge about assessment of Reading based HOTS (Higher Order Thinking Skill) Based optimizing literacy